Pengaruh Brand Ambassador Terhadap Minat Beli Produk Maybelline New York Melalui Sikap pada Iklan Sebagai Variabel Mediasi - Marischa Aqilah Faradilla; Sonja Andarini (JURNAL ADMINISTRASI BISNIS, 2022)
Maybelline New York is one of the most famous cosmetic products, one of which is in Indonesia. Maybelline New York has issued more than 200 cosmetic products by utilizing the latest technological sophistication in the latest trends. Just like any other cosmetic business, Maybelline New York certainly wants its product sales to always increase, but in fact there has been a decline in sales in recent years. This study aims to determine the effect of the brand ambassador "ITZY" on buying interest in Maybelline New York products through attitudes to advertising as a mediating variable. This research is a type of quantitative research with explanatory research method. In sampling the technique used is purposive sampling technique with a sample of 100 respondents. Data analysis was performed using the Partial Least Square-Structural Equation Modeling (PLS-SEM) model with the help of SmartPLS 3.0 software. The results showed that the brand ambassador had a significant effect on buying interest; brand ambassador has a significant effect on attitudes in advertising; attitude to advertising has a significant effect on buying interest; attitude to advertising has a significant effect in mediating the influence of brand ambassadors on buying interest in Maybelline New York products